Usability Testing of â€œCHIselâ€: Cultural Heritage Information System Extended Layers of Interactive 3D Computer Generated Images and Relational Database - G., Tromp, J; Chowdhury, J; C. Torres, J; Thi My, Hoang (International Journal of Engineering and Technology, 2018)
CHISel is a cultural heritage information system that supports the extensive organization, tracking, and implementation of data on 3D computer generated models of archaeological artefacts and site. We conducted a detailed user test of CHISel, to assess the usability of the complex and numerous system features, in order to assess the efficiency, user satisfaction, memorability, learnability, and accuracy. These qualities are particularly crucial to software like CHISel, which has a high learning curve for new and inexperienced users, involves professional, field-specific users, requires high-precision, high accuracy and contains a large amount of complex system features that must function well in order for the program to work as an apt integrative system.Â Â